Eosinophil granulocytes are activated during the remission phase of ulcerative colitis. Issue 12 (10th May 2005) - Lampinen, M; Rönnblom, A; Amin, K; Kristjansson, G; Rorsman, F; Sangfelt, P; Säfsten, B; Wagner, M; Wanders, A; Winqvist, O; Carlson, M
Abstract : Aim: The aim of this study was to establish a method of investigating intestinal eosinophil and neutrophil granulocytes by flow cytometry, and to compare the distribution and activity of these cells in different stages of ulcerative colitis (UC). Methods: Biopsy samples were taken from six locations of the entire colon and from the terminal ileum in 10 patients with active total UC, 10 patients with inactive total UC, eight patients with active distal UC, and 11 control subjects. Cell suspensions from biopsies and from peripheral blood were incubated with fluorophore conjugated monoclonal antibodies. The use of scatter plot-gating and specific antibodies was established in a flow cytometry assay. Results: Eosinophils were more numerous and more active in patients with active UC than in controls. Interestingly, during inactive UC, the number of activated eosinophils was even larger. Eosinophil activity was high in the rectum of patients with distal colitis but was also slightly elevated in the proximal colon. Neutrophils were increased in number and activity during active but not inactive UC. In patients with distal colitis, activated neutrophils were only found in the sigmoid colon and rectum. Conclusion: With this method, we confirm that neutrophils participate in the inflammatory process during active UC, and that they express a resting phenotype during remission. The finding of activated eosinophils in inflamed intestine strengthens the view of these cells as proinflammatory and tissue damaging. Nevertheless, our new finding of high eosinophil activation during inactive UC suggests that eosinophils play a role in repair of injured epithelium.